Biotechnological Approach for the Production of Prebiotics and Search for New Probiotics and their Application in the Food Industry - Daniela Iga Buitrón (Applied Food Biotechnology, 2018)
Background and objective: Prebiotics and probiotics intake have been widely recognized in past recent years due to possessing multiple health benefits. Prebiotics are non-digestible carbohydrates that promote the growth and/or activity of beneficial bacteria in the colon which improves the health. Moreover, the incorporation of probiotics in food has also been a growing practice due to its immunomodulatory effect, the production of organic acids and other compounds that promotes the absorption of nutrients and the general health of the digestive system.